Preparation method and application of Bi-series semiconductor modified hydrotalcite composite material

By modifying the nano-scale Bi-based semiconductor catalyst on the surface of the hydrotalcite material, forming Bi-based semiconductor-modified hydrotalcite composite materials, the problems of insufficient photocatalytic activity of bismuth oxyhalide and low absorption rate of hydrotalcite for visible light are solved, and high efficiency is achieved Photocatalytic degradation effect.

CN119425741APending Publication Date: 2025-02-14SHIJIAZHUANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411567051.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the photocatalysis process, a single bismuth oxyhalide material has problems such as high photogenerating electron-hole recombination rate and insufficient catalytic activity, and the hydrotalcite has a low absorption rate of visible light.

Method used

By uniformly modifying the nano-scale Bi-based semiconductor catalyst to the surface of the hydrotalcite material, a Bi-based semiconductor modified hydrotalcite composite material is formed, and the layered structure of hydrotalcite forms a synergistic effect with bismuth oxyhalide to improve photocatalytic performance.

Benefits of technology

It significantly improves the photocatalytic efficiency and visible light absorption utilization rate, has good catalytic degradation effect on pollutants in water, is simple to operate, easy to obtain raw materials, and short preparation period.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425741A_ABST
    Figure CN119425741A_ABST
Patent Text Reader

Abstract

The invention relates to a Bi-series semiconductor modified hydrotalcite composite material preparation method, which comprises: mixing magnesium chloride hexahydrate and aluminum nitrate nonahydrate, adding into water, and uniformly mixing to prepare a solution A; mixing anhydrous sodium carbonate and sodium hydroxide, adding water, and uniformly mixing to prepare a solution B; adding the solution B into the solution A to obtain a mixed solution C; carrying out constant-temperature aging and suction filtration on the mixed solution C, and drying, grinding and sieving the left precipitate to prepare magnesium-aluminum hydrotalcite; bismuth nitrate pentahydrate and magnesium aluminum hydrotalcite are added into water to serve as a solution D; a surfactant with halide ions is selected and dissolved in an organic solvent to serve as a solution E, then the solution E is dropwise added into the solution D in the stirring state, stirring continues after dropwise adding is completed, finally, the reaction liquid continues to react, and washing and drying are conducted. The invention further relates to application of the Bi-series semiconductor modified hydrotalcite composite material, and the Bi-series semiconductor modified hydrotalcite composite material is used for treating dye wastewater. The preparation method is high in visible light absorption and utilization rate, simple in preparation and short in preparation time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalysis, and specifically relates to a preparation method and application of a Bi-based semiconductor modified hydrotalcite composite material. Background Art

[0002] The chemical industry is developing rapidly, but industrial wastewater has caused serious environmental pollution. In the field of wastewater treatment, photocatalytic technology is considered to be an emerging technology with broad application prospects. This technology is easy to operate and has relatively low energy consumption. Especially when using sunlight as a light source, it has the advantages of environmental protection and sustainability. Photocatalytic degradation of organic matter in wastewater is pollution-free and highly efficient, and has good development prospects.

[0003] Bismuth oxyhalide is a commonly used photocatalyst with good chemical stability, can efficiently utilize sunlight, is non-toxic and difficult to decompose in aqueous solution, and is harmless to the environment. It has a strong ability to photocatalytically degrade organic matter and can effectively achieve the purpose of degrading organic matter. Therefore, it has broad application prospects in the fields of environmental governance and energy conversion. Specifically, the applications of bismuth oxyhalide are as follows: 1. Degradation of organic pollutants: In the presence of visible light, bismuth oxyhalide can decompose organic pollutants into harmless substances, such as carbon dioxide and water molecules. Its catalytic efficiency is higher than that of commercial photocatalyst titanium dioxide, so it has important applications in sewage purification.

[0004] 2. Gas detection: In the field of gas sensing, the special photocatalytic properties of bismuth oxyhalide can realize sensitive detection of certain gases.

[0005] 3. Cosmetics: In the field of cosmetics, bismuth oxyhalide can be used as a new type of additive to improve the performance and stability of cosmetics by using its photocatalytic properties. It can be seen that the photocatalytic application of bismuth oxyhalide is wide, and it is very meaningful to improve its photocatalytic performance. Ge Jianyu et al. used a hydrothermal method to adjust Fe 3+ / Bi 3+ BiOBr catalysts with different doping amounts were synthesized by the molar ratio of substances. Through photocatalytic experiments, it was found that the photocatalytic performance of 7% Fe doping was better. At the same time, under the irradiation of the same light source, after doping BiOBr catalyst, the degradation rate increased from 62.82% to 89.66%, the light absorption capacity was enhanced, and the photogenerated carrier transfer was more efficient. Yang Ziyi and others used silver and cobalt as dopants, prepared pure BiOBr by hydrothermal method, and then studied the photocatalytic performance under ultraviolet light. By adding 15% Ag, the degradation rate increased from 45.14% to 47.33%. The results show that the degradation rate of BiOBr doped with a certain amount of metal is higher.

[0006] Single bismuth oxyhalide materials still have problems such as high photogenerated electron-hole recombination rate and insufficient catalytic activity during the photocatalytic process.

[0007] LDH is a type of anionic layered double hydroxide. These structures usually use magnesium oxide octahedron (MgO6) as the basic unit and share edge formation layers. Thanks to their unique chemical composition and microstructure, LDH exhibits advantages such as anion exchange capacity, selective adsorption characteristics, large specific surface area, adjustable layer composition, good catalytic performance and excellent thermal stability. In the field of catalysis, magnesium aluminum hydrotalcite (MgAl-LDH) exhibits high specific surface area, good stability, and it can not only be used as a catalyst but also as a catalyst carrier, with adjustable composition, interlayer anion exchange, alkaline sites, and environmental friendliness. Many advantages make it a hot spot in the field of photocatalysis and an important material for industrial applications. However, single LDH has the problem of low visible light absorption utilization. Summary of the invention

[0008] To solve the above problems, the purpose of the present invention is to provide a preparation method and application of a Bi-based semiconductor-modified hydrotalcite composite material, which utilizes the layered structure characteristics of hydrotalcite and its photocatalytic performance to form a synergistic effect with bismuth oxyhalide to improve the photocatalytic performance, has a high visible light absorption utilization rate, is simple to prepare, and has a short preparation time, and is used for the degradation of dye wastewater.

[0009] The technical solution adopted by the present invention to achieve its purpose is: A preparation method of a Bi-based semiconductor-modified hydrotalcite composite material comprises the following steps: S1, mixing magnesium chloride hexahydrate and aluminum nitrate nonahydrate, adding water thereto and mixing them uniformly to prepare solution A; mixing anhydrous sodium carbonate and sodium hydroxide, adding water thereto and mixing them uniformly to prepare solution B; adding solution B to solution A to obtain a mixed solution C; aging the mixed solution C at a constant temperature, filtering after aging, washing, drying, grinding and sieving the remaining precipitate to obtain magnesium-aluminum hydrotalcite; S2. Add bismuth nitrate pentahydrate and magnesium aluminum hydrotalcite into water as solution D; select a surfactant with halogen ions and dissolve it in an organic solvent as solution E, then add solution E dropwise into solution D under stirring, continue stirring after the addition is completed, and finally continue to react the reaction liquid. After the reaction is completed, wash and dry to obtain a Bi-based semiconductor modified hydrotalcite composite material.

[0010] The molar ratio of magnesium chloride hexahydrate: aluminum nitrate nonahydrate: water in solution A in S1 is: 2.5:1:417-500; Preferably, the molar ratio of magnesium chloride hexahydrate: aluminum nitrate nonahydrate: water in solution A in S1 is: 2.5:1:417; The molar ratio of anhydrous sodium carbonate: sodium hydroxide: water in solution B is: 1:16:417-500; Preferably, the molar ratio of anhydrous sodium carbonate: sodium hydroxide: water in solution B is: 1:16:417; The temperature of the mixed solution C during constant temperature aging is 55-65°C, the time of constant temperature aging is 8-12 hours, and the pressure of constant temperature aging is room temperature.

[0011] The molar ratio of aluminum nitrate nonahydrate to anhydrous sodium carbonate is 2.01:1.

[0012] Preferably, the washing in S1 is performed with distilled water until the pH is equal to 7; The drying temperature is 90-120°C and the drying time is 4-10 hours; The sieve used for screening is 80-100 mesh.

[0013] The mass ratio of bismuth nitrate pentahydrate: magnesium aluminum hydrotalcite: water in S2 is 4.85:3.33:15-20; Preferably, the mass ratio of bismuth nitrate pentahydrate: magnesium aluminum hydrotalcite: water in S2 is 4.85:3.33:15; The surfactant having halogen ions is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide; The organic solvent is one or two of ethanol and carbon tetrachloride; The molar ratio of the halide ion surfactant: the organic solvent is 1:84-90; Preferably, the molar ratio of the halide ion surfactant: the organic solvent is 1:84; The molar ratio of bismuth nitrate pentahydrate to the surfactant having halogen ions is 1:1; After the addition is completed, stirring is continued for 20-60 minutes; The reaction time is 18-28 hours, and the reaction temperature is 120-160°C.

[0014] Preferably, the dripping speed of adding solution E to D in S2 is about 5-6 drops / s.

[0015] Preferably, the washing in S2 is performed by alternating deionized water and anhydrous ethanol for at least 2 times; The drying temperature in S2 is 75-85°C and the drying time is 6-12h.

[0016] Preferably, the water in S1 and S2 is distilled water.

[0017] The invention discloses an application of a Bi-based semiconductor modified hydrotalcite composite material for treating dye wastewater.

[0018] Preferably, the method comprises the following steps: adding the Bi-based semiconductor modified hydrotalcite composite material into dye wastewater, ultrasonicating for 30-60 minutes in a dark environment, then photocatalytically degrading the composite material under visible light conditions, and measuring the degradation efficiency by a UV-visible spectrophotometer.

[0019] Preferably, the mass ratio of Bi-based semiconductor modified hydrotalcite composite material to dye wastewater is 1:1000; The concentration of dye wastewater is 0.01g / L; The degradation time is 0-120 min, preferably 120 min.

[0020] The beneficial effects of the present invention are: The present invention uniformly modifies the surface of a hydrotalcite material with a layered structure by nano-scale Bi-based semiconductor catalysts, which not only increases its specific surface area and provides more active sites, but also improves the separation efficiency of photogenerated carriers and the photocatalytic efficiency. The Bi-based semiconductor-modified hydrotalcite composite material has a good catalytic degradation effect on water pollutants such as rhodamine B and methylene blue under visible light irradiation. The preparation method of the present invention is simple to operate, the raw materials are easily available, the preparation cycle is short, the visible light catalytic efficiency is high, and it has broad application prospects in the field of photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The figures are scanning electron microscope images of Example 1 of the present invention; wherein, (a) BiOCl, (b) MgAl-LDH, (c) 10% BiOCl / MgAl-LDH, (d-f) 25% BiOCl / MgAl-LDH are scanning electron microscope images at different magnifications; (d) the magnification is 1.1K, (e) the magnification is 22K, and (f) the magnification is 60K.

[0022] Figure 2 1 is the XRD diagram of MgAl-LDH, BiOBr / MgAl-LDH and BiOBr in the examples of the present invention.

[0023] Figure 3 This is a degradation curve diagram of Rhodamine B by BiOCl / MgAl-LDH of the present invention.

[0024] Figure 4 This is a graph showing the results of a control experiment on the degradation of methylene blue by BiOBr / MgAl-LDH composites with different loading amounts in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] Example 1 S1. Use weighing paper to weigh 4.88g MgCl2.6H2O, 3.00g Al(NO3)3.9H2O, 0.42g anhydrous sodium carbonate (NaCO3), and 2.56g sodium hydroxide (NaOH). Pour MgCl2.6H2O and Al(NO3)3.9H2O into a beaker, add 60ml of distilled water to prepare solution A; put NaCO3 and NaOH into a beaker together, add 30ml of distilled water to stir, and prepare solution B; slowly add B to A on a digital constant temperature magnetic stirrer to obtain a mixed solution C; put it into a reactor, and put the reactor in an electric blast drying oven at 60℃ for aging for 10 hours; after aging, use a circulating water vacuum pump to filter, leaving the precipitate and wash it with distilled water until the pH is equal to 7, take out the precipitate and put it into an electric blast drying oven at 100℃ to dry for 6 hours. After drying, grind it and pass it through an 80-mesh sieve to obtain magnesium aluminum hydrotalcite. Figure 1 (b) shown.

[0027] S2. Weigh 10 mmol Bi(NO3)3·5H2O and dissolve it in 15 ml deionized water. Weigh 3.33 g of the prepared MgAl-LDH and add it to the Bi(NO3)3·5H2O solution. Stir it on a magnetic stirrer for 0.5 h. Slowly add 5-6 drops / s of a mixture of 0.01 mol of hexadecyltrimethylammonium chloride and 50 ml of anhydrous ethanol to the mixed solution. Stir it on a magnetic stirrer for 0.5 h. After stirring, pour the suspension into a polytetrafluoroethylene autoclave, seal it, and put it in an oven (140°C, 24 h). After the reaction is completed, cool it to room temperature and remove it from the oven. Centrifuge it and take out the precipitate. Rinse it twice with deionized water and anhydrous ethanol respectively. Put it in an oven to dry (80°C, 12 h). After drying, grind it into powder, i.e., BiOCl / MgAl-LDH complex. By using the above method, the BiOCl modification amount was 10% [such as Figure 1 (c)], 15%, 20%, 25% [as shown Figure 1 (d-f)] and 30% BiOCl / MgAl-LDH composite.

[0028] S3. The preparation of BiOCl is the same as step S2, except that the addition of MgAl-LDH is omitted. Figure 1 (a) shown.

[0029] Example 2 The difference between this embodiment and embodiment 1 is that the operation of step S2 is repeated to replace hexadecyltrimethylammonium chloride with hexadecyltrimethylammonium bromide to prepare the BiOBr / MgAl-LDH complex. By changing the mass of BiOBr, BiOBr modification amounts of 10%, 20%, 30%, 40%, and 50% are prepared respectively. Figure 2 shown.

[0030] Example 3 S1. Weigh 4.88g MgCl2.6H2O, 3.00g Al(NO3)3.9H2O, 0.42g anhydrous sodium carbonate (NaCO3), and 2.56g sodium hydroxide (NaOH) using weighing paper. Pour MgCl2.6H2O and Al(NO3)3.9H2O into a beaker, add 72ml de-distilled water to prepare solution A; put NaCO3 and NaOH into a beaker, add 36ml distilled water to stir, and prepare solution B; slowly add B into A on a digital constant temperature magnetic stirrer to obtain mixed solution C; put it into a reactor, and put the reactor into an electric hot air drying oven at 55℃ for aging for 8 hours; after aging, use a circulating water vacuum pump to filter, leave the precipitate and wash it with de-distilled water until the pH is equal to 7, take out the precipitate and put it into an electric hot air drying oven at 120℃ for 4 hours, grind it after drying, and pass it through an 80-mesh sieve to obtain magnesium aluminum hydrotalcite.

[0031] S2. Weigh 10 mmol Bi(NO3)3·5H2O and dissolve it in 20 ml deionized water. Weigh 3.33 g of the prepared MgAl-LDH and add it to the Bi(NO3)3·5H2O solution. Stir it on a magnetic stirrer for 0.5 h. Slowly add 5-6 drops / S of a mixture of 0.01 mol of hexadecyltrimethylammonium bromide and 48 ml of carbon tetrachloride to the mixed solution. Stir it on a magnetic stirrer for 1 h. After stirring, pour the suspension into a polytetrafluoroethylene autoclave, seal it, and put it in an oven (120°C, 28 h). After the reaction is completed, cool it to room temperature and remove it from the oven. Centrifuge it and take out the precipitate. Rinse it twice with deionized water and anhydrous ethanol respectively. Put it in an oven to dry (85°C, 6 h). After drying, grind it into powder, i.e., BiOBr / MgAl-LDH complex. Using the above method, BiOBr / MgAl-LDH composites with BiOBr modification amounts of 10%, 15%, 20%, 25% and 30% were prepared by changing the mass of BiOBr.

[0032] Example 4 S1. Weigh 4.88g MgCl2.6H2O, 3.00g Al(NO3)3.9H2O, 0.42g anhydrous sodium carbonate (NaCO3), and 2.56g sodium hydroxide (NaOH) using weighing paper. Pour MgCl2.6H2O and Al(NO3)3.9H2O into a beaker, add 70ml of deionized water to prepare solution A; put NaCO3 and NaOH into a beaker, add 32ml of distilled water to stir, and prepare solution B; slowly add B into A on a digital constant temperature magnetic stirrer to obtain mixed solution C; put it into a reactor, and put the reactor into an electric hot air drying oven at 65℃ for constant temperature aging for 12 hours; after aging, use a circulating water vacuum pump to filter, leave the precipitate and wash it with deionized water until the pH is equal to 7, take out the precipitate and put it into an electric hot air drying oven at 90℃ for drying for 10 hours, grind it after drying, and pass it through a 100-mesh sieve to obtain magnesium aluminum hydrotalcite.

[0033] S2. Weigh 10 mmol Bi(NO3)3·5H2O and dissolve it in 18 ml deionized water. Weigh 3.33 g of the prepared MgAl-LDH and add it to the Bi(NO3)3·5H2O solution. Stir it on a magnetic stirrer for 0.5 h. Slowly add 5-6 drops / s of a mixture of 0.01 mol of hexadecyltrimethylammonium chloride and 51.5 ml of anhydrous ethanol to the mixed solution. Stir it on a magnetic stirrer for 20 min. After stirring, pour the suspension into a polytetrafluoroethylene autoclave, seal it, and put it in an oven (160°C, 18 h). After the reaction is completed, cool it to room temperature and remove it from the oven. Centrifuge it and take out the precipitate. Rinse it twice with deionized water and anhydrous ethanol respectively. Put it in an oven to dry (75°C, 12 h). After drying, grind it into powder, i.e., BiOCl / MgAl-LDH complex. Using the above method, BiOCl / MgAl-LDH composites with BiOCl modification amounts of 10%, 15%, 20%, 25% and 30% were prepared by changing the mass of BiOCl.

[0034] Application Example 1 Weigh 0.10g BiOCl / MgAl-LDH complex (Example 1), add 100 mL 0.01g / L Rhodamine B solution, first perform ultrasonic dark reaction in a lightless environment for half an hour to allow the Rhodamine B adsorbed by the sample to reach equilibrium, take a sample once, place it in a centrifuge tube, turn on the halogen tungsten lamp for illumination, and add a filter above the beaker to filter light other than visible light. Take 5 mL of the sample every 15 minutes and place it in a centrifuge tube, put the centrifuge tube into a high-speed desktop centrifuge for centrifugation for 5 minutes, take the supernatant, put it in a quartz cuvette, and use a UV-visible spectrophotometer for spectral scanning. The reaction ends after 2 hours, and the degradation rate is calculated using the formula.

[0035] Degradationrate=(C0-C) / C0×100%.

[0036] like Figure 3 As shown, the degradation rates of the composites when the BiOCl modification amounts were 10%, 15%, 20%, 25% and 30% were 65.6%, 75.6%, 99.1%, 85.6% and 78%, respectively.

[0037] Application Example 2 Weigh 0.10g BiOBr / MgAl-LDH complex (Example 2), add 100 mL 0.01g / L methylene blue solution, first perform ultrasonic dark reaction in a lightless environment for half an hour to allow the methylene blue adsorbed by the sample to reach equilibrium, take a sample once, place it in a centrifuge tube, turn on the halogen tungsten lamp for illumination, and add a filter above the beaker to filter out light other than visible light. Take 5 mL of the sample every 15 minutes and place it in a centrifuge tube, put the centrifuge tube into a high-speed desktop centrifuge for centrifugation for 5 minutes, take the supernatant, put it in a quartz cuvette, and use a UV-visible spectrophotometer for spectral scanning. The reaction ends after 2 hours, and the degradation rate is calculated using the formula.

[0038] Degradationrate=(C0-C) / C0×100%.

[0039] like Figure 4 As shown, the degradation rates of the composites when the BiOBr modification amounts were 10%, 20%, 30%, 40% and 50% were 71.9%, 77.14%, 94.21%, 83.21% and 78.41%, respectively.

[0040] The above description is only a preferred specific implementation manner of the present invention; however, the protection scope of the present invention is not limited thereto; any technician familiar with the technical field within the technical scope disclosed by the present invention; any equivalent replacement or change based on the technical solution and improved concept of the present invention shall be covered by the protection scope of the present invention.

Claims

1. A method for preparing a Bi-based semiconductor-modified hydrotalcite composite material, characterized in that: The following steps are involved: S1. Mix magnesium chloride hexahydrate and aluminum nitrate nonahydrate, add water thereto and mix well to prepare solution A; mix anhydrous sodium carbonate and sodium hydroxide, add water thereto and mix well to prepare solution B; add solution B to solution A to obtain a mixed solution C; age the mixed solution C at a constant temperature, filter it after aging, wash, dry, grind and sieve the precipitate, and obtain magnesium aluminum hydrotalcite; S2. Add bismuth nitrate pentahydrate and magnesium aluminum hydrotalcite into water as solution D; select a surfactant with halogen ions and dissolve it in an organic solvent as solution E, then add solution E dropwise into solution D under stirring, continue stirring after the addition is completed, and finally continue to react the reaction liquid. After the reaction is completed, wash and dry to obtain a Bi-based semiconductor modified hydrotalcite composite material.

2. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: The molar ratio of magnesium chloride hexahydrate: aluminum nitrate nonahydrate: water in solution A in S1 is: 2.5:1:417-500; The molar ratio of anhydrous sodium carbonate: sodium hydroxide: water in solution B is: 1:16:417-500; The temperature of the mixed solution C is 55-65°C, and the time of the constant temperature aging is 8-12 hours; The molar ratio of aluminum nitrate nonahydrate to anhydrous sodium carbonate is 2.01:

1.

3. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: Wash in S1 with distilled water until the pH is equal to 7; The drying temperature is 90-120°C and the drying time is 4-10 hours; The sieve used for screening is 80-100 mesh.

4. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: The mass ratio of bismuth nitrate pentahydrate: magnesium aluminum hydrotalcite: water in S2 is 4.85:3.33:15-20; The surfactant having halogen ions is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide; The organic solvent is one or two of ethanol and carbon tetrachloride; The molar ratio of the halide ion surfactant: the organic solvent is 1:84-90; The molar ratio of bismuth nitrate pentahydrate to the surfactant having halogen ions is 1:1; After the addition is completed, stirring is continued for 20-60 minutes; The reaction time is 18-28 hours, and the reaction temperature is 120-160°C.

5. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: In S2, solution E is added dropwise to D at a rate of about 5-6 drops / s.

6. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: The washing in S2 is performed by washing with deionized water and anhydrous ethanol alternately for at least 2 times; The drying temperature in S2 is 75-85°C and the drying time is 6-12h.

7. The method for preparing a Bi-based semiconductor-modified hydrotalcite composite material according to claim 1, characterized in that: The water in S1 and S2 is distilled water.

8. An application of a Bi-based semiconductor modified hydrotalcite composite material, prepared by the preparation method of a Bi-based semiconductor modified hydrotalcite composite material according to claim 1, characterized in that: Used for the treatment of dye wastewater.

9. The use of a Bi-based semiconductor-modified hydrotalcite composite material according to claim 8, characterized in that: The method comprises the following steps: adding a Bi-based semiconductor modified hydrotalcite composite material into dye wastewater, ultrasonicating for 30-60 minutes in a dark environment, then photocatalytically degrading the composite material under visible light conditions, and measuring the degradation efficiency by an ultraviolet-visible spectrophotometer.

10. The use of a Bi-based semiconductor-modified hydrotalcite composite material according to claim 8, characterized in that: The mass ratio of Bi-based semiconductor modified hydrotalcite composite material: dye wastewater is 1:1000; The concentration of dye wastewater is 0.01g / L; The degradation time is 0-120min.